On Parity of Esteem between Vocational and General Academic Programs in Upper Secondary Education in Iceland - Eiríksdóttir, Elsa; Ragnarsdóttir, Guðrún; Jónasson, Jón Torfi (Menntavísindasvið Háskóla Íslands, 2020)
In a European context, there has long been a discussion on the problem of parity of esteem between vocational education and training (VET) and general academic upper secondary education (see for example CEDEFOP, 2014; Lasonen & Young, 1998; Parkes, 1993). VET education does not enjoy the same status as general academic upper secondary education, which usually provides a pathway to higher education. The disparity of esteem between these two educational pathways reveals itself, for example, in differences in social standing, content taught, and the ability of students entering the programs. This, in turn, has consequences for social justice and future prospects of students (Nylund et al., 2018).The disparity of esteem has been debated in Iceland for the better part of a century (Jón Torfi Jónasson, 1994). Despite regular declarations from various stakeholders of the need to strengthen VET, little has changed over the years. Jón Torfi Jónasson (1998a) identified the diverse forces working against VET at the upper secondary level in Iceland, some including the very stakeholders vowing support. There have been several attempts to address the apparent parity divide, showing a variety of very deliberate attempts to de-institutionalize the divide between vocational and academic tracks. The most recent examples are the educational reform in Iceland in 2008 and a curriculum overhaul in 2011 (lög um framhaldsskóla [Upper Secondary Education Act] nr. 92/2008; Mennta- og menningarmálaráðuneytið [Ministry of Education, Science and Culture], 2012). A white paper on education reform (Menntaog menningarmálaráðuneytið [Ministry of Education, Science and Culture], 2014), also presented a clear policy directive to enhance the status of vocational education. Despite these efforts, a disparity in esteem between vocational and general academic pathways seems evident and the resilience of the issue begs further investigation.The aim of the paper is to explore the disparity between vocational and academic programs in contemporary ...